2019
DOI: 10.3390/nano9081109
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Hierarchical rGO/PANI@PtNi Nanocomposite via Microwave-Assisted Treatment for Non-Enzymatic Detection of Hydrogen Peroxide

Abstract: A hierarchical composite based on the modified reduced graphene oxide with platinum-nickel decorated polyaniline nano-spheres (rGO/PANI@PtNi) was facilely prepared via microwave-assisted self-reduction for an application in nonenzymatic hydrogen peroxide (H2O2) detection. Compared to the pristine rGO, the composite exhibited a much tougher surface due to the stacking of conductive PANI nano-spheres on rGO sheets, leading to good dispersion of PtNi nanoparticles and a large active area. Furthermore, the multi-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 81 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…This indicates an excellent degree of alloying between Pt, Ni, and Co [ 46 ]. The XRD results showed that the diffraction peaks of Ni and Co in composites are not obvious and may be related to the small amount of Ni and Co in composites [ 47 , 48 , 49 ]. However, the presence of Ni and Co can also be explained by a slight shift of the Pt (111) peak to a higher angle in the XRD analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates an excellent degree of alloying between Pt, Ni, and Co [ 46 ]. The XRD results showed that the diffraction peaks of Ni and Co in composites are not obvious and may be related to the small amount of Ni and Co in composites [ 47 , 48 , 49 ]. However, the presence of Ni and Co can also be explained by a slight shift of the Pt (111) peak to a higher angle in the XRD analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Supporting Materials can stabilize M-NPs, allowing for easier handling of the M-NPs and providing for additional tuning options for applications. Carbon materials as support for Pt-NPs are commonly used in the field of electrochemistry because of their high electrical conductivity, low weight, low cost, easy production, and manifold structures [ 6 , 19 ]. Our group has already shown the usage of (thermally) reduced graphite oxide (rGO, also known as TRGO) as M-NP support [ 20 , 21 ], which also offers remarkable properties as support for electrode materials [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has already shown the usage of (thermally) reduced graphite oxide (rGO, also known as TRGO) as M-NP support [ 20 , 21 ], which also offers remarkable properties as support for electrode materials [ 22 , 23 , 24 ]. rGO increases the electrochemical activity of Pt-NPs [ 19 ], stabilizes very small M-NPs [ 25 , 26 ], and offers improved protection for supported NPs against poisoning, compared with available standard carbon black materials [ 20 ]. Since rGO provides less functional groups that can interact with M-NPs than graphite oxide, the deposition of Pt-NPs on rGO (Pt-NP@rGO) in ILs remains difficult and was only successful after additional rGO functionalization with thiol groups [ 20 ] to improve the interaction between Pt-NPs and its support.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate concentrations of ROS can correctly activate cellular antioxidant defense mechanisms and ROS can participate in immune and signal transduction processes in vivo [ 4 , 5 ], while the accumulation of ROS can cause the risk of cardiovascular disease and even cancer [ 6 ]. Several different approaches have been developed for the detection of ROS in vivo or in vitro [ 7 , 8 ], mainly electrochemical and optical methods, including fluorescence [ 9 , 10 ], surface plasmon resonance [ 11 ], and Raman spectroscopy [ 12 , 13 ]. However, each method has disadvantages, such as excessive background signals, tedious sample processing, high running cost, etc., which restrict their widespread application.…”
Section: Introductionmentioning
confidence: 99%